Relationship between knowledge of patient safety and its implementation in the hospital - Diyah Yulistika Handayani; Etlidawati (UM Purwokerto Press, 2020)
The patient safety in hospitals is often not optimally implemented due to the imperfect roles of nurses to implement the patient safety. Errors that result in injured patients can be due to inaccurate identification of patients. As a result, it triggers to delays in diagnosis, failure in action, medication errors and dosage errors when administering drugs. In 2016, it was found 11 nurses experiencing needle stick injury. This occurs due to wrong method of re-inserting the needle into the syringe that is used by using two hands. It also occurred in 2018, based on K3 RS report, there were 9 nurses experiencing needle stick injury.This research aims to find out if there is a relationship between nurses' knowledge about patent safety and its implementation the inpatient room of Purwokerto Hospital.This is a qualitative research method with a cross-sectional approach. The samples of this study are nurses 35 nurses as respondents in the inpatient room of RSI Purwokerto. Chi-square test is used as data analysis.It is found that 25 respondents (71.4%) have good knowledge of patient safety, while 10 respondents (28.6%) are in moderate category (good enough). 16 respondents (45.7%) have implemented the patient safety well, and 19 respondents (54.3%) have carried out it quiet well. Based on the statistical test, the p value is 0.408. Which is <of 0.05.so there is no relationship between patient safety knowledge and the implementation of patient safety.There is no relationship between the knowledge about patient safety and the implementation of of patient safety in the inpatient room of hospital in Purwokerto Hospital.